2014
DOI: 10.1111/1755-5922.12095
|View full text |Cite
|
Sign up to set email alerts
|

Different Effects of Fenofibrate on Metabolic and Cardiovascular Risk Factors in Mixed Dyslipidemic Women With Normal Thyroid Function and Subclinical Hypothyroidism

Abstract: SUMMARYAims: Subclinical hypothyroidism is suggested to increase cardiovascular risk. No previous study compared the effect of any fibrate on plasma levels of lipids and other cardiovascular risk factors in patients with different thyroid function status. Methods: The study included three age-, weight-and lipid-matched groups of women with mixed dyslipidemia in different thyroid function status: patients with untreated subclinical hypothyroidism (group 1, n = 18), women with treated hypothyroidism (group 2, n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 40 publications
1
8
1
Order By: Relevance
“…Previously, we observed a multidirectional action of fenofibrate including an improvement in glucose metabolism and the inhibitory action on plasma lipids and other risk factors in various metabolic disturbances, including prediabetes, overt diabetes, and mixed dyslipidemia [20][21][22][23][24]. However, the present study is the first which has shown a beneficial effect of any fibrate in patients with hypogonadism.…”
Section: Discussioncontrasting
confidence: 46%
“…Previously, we observed a multidirectional action of fenofibrate including an improvement in glucose metabolism and the inhibitory action on plasma lipids and other risk factors in various metabolic disturbances, including prediabetes, overt diabetes, and mixed dyslipidemia [20][21][22][23][24]. However, the present study is the first which has shown a beneficial effect of any fibrate in patients with hypogonadism.…”
Section: Discussioncontrasting
confidence: 46%
“…Recently, we have found that the effect of atorvastatin as well as fenofibrate, which is another lipid‐lowering drug with pleiotropic effects, on plasma lipids and circulating levels of cardiometabolic risk factors partially depended on hypothalamic‐pituitary‐thyroid axis activity and was more pronounced in patients with normal thyroid function than in patients with untreated subclinical hypothyroidism. A possible association between vitamin D and vascular disease suggests that the effects of hypolipidemic agents may also be determined by the amount of this vitamin.…”
Section: Introductionmentioning
confidence: 99%
“…Despite these obvious benefits, statin therapy seems to be associated with a slightly increased risk of development of diabetes [13,14]. An improvement in glucose homeostasis was, in turn, induced by peroxisome proliferator-activated receptor-a (PPARa) activators (fibrates) [15][16][17][18], but the favourable effect of this group of hypolipidaemic agents on cardiovascular morbidity and mortality was observed only in some studies [19,20]. Moreover, no large clinical study has investigated the relationship between age and clinical effectiveness of PPARa activators or included only older adults.…”
Section: Introductionmentioning
confidence: 99%